Q-switched erbium doped fiber laser incorporating zinc oxide in polyvinyl alcohol as passive saturable absorber - Norizan, Nurul Alina Afifi; Lokman, Muhammad Quisar; Zuikafly, Siti Nur Fatin; Yahaya, Hafizal; Ahmad, Fauzan; Harun, Sulaiman Wadi (Universiti Teknikal Malaysia Melaka, 2018)
The search for the ideal saturable absorber in realizing a better pulsed laser is still on-going. With a wider bandgap, zinc oxide promises better laser performance in terms of higher stability, better temperature durability, and higher power operation. These properties were clearly demonstrated using a Q-switched Erbium-doped fiber laser residing a newly fabricated Zinc Oxide embedded in polyvinyl alcohol (ZnO-PVA) based film as a passive saturable absorber in a ring laser cavity. The surface morphology of the fabricated ZnO-PVA film shows a thoroughly mixed composite with a measured film thickness of 22 µm. The Q-switched laser operates at 1557.6 nm within a tunable input pump power from 23.8 mW to 134.8 mW. At maximum input pump power, the generated pulse produce shortest pulse width, maximum repetition rate, maximum instantaneous peak power maximum pulse energy of 4.52 s, 71.84 kHz, 6.7 mW and 31.6 nJ, respectively. The first beat note of the measured signal to ratio is around 61 dB, which indicates the stability of the generated pulse. The proposed Q-switched laser can be further improved and can find potential application in metrology, fiber sensor, medical diagnostics and the most commonly known optical communication.